Faktor- Faktor yang Berhubungan dengan Keluhan Nyeri Punggung Bawah pada Pekerja Welding - Noviyanti; Yessi Azwar; Eva Santi Hutasoit; Dwi Tegar Larasati (HEALTH CARE : JURNAL KESEHATAN, 2021)
Low back pain is the musculoskeletal disorders caused by poor body activity. The purpose of this research is to know the factors related to low back pain complaints on welding workers at PT X Batam City. This type of research uses descriptive analytical and uses a quantitative approach using a cross sectional design. The sample in this study were 85 workers in the Welding section of PT X. The sampling technique in this study is Total Sampling and statistical analysis using Chi-Square test. The results of the research from 85 respodents found that 48 respondents (56,5%) had experienced low back pain. Respondents with age category over 35 years were 48 respondents (56,6%), Respondents with BMI category overweight were 35 respondents (41,2%), Respondents with smoking category were 59 respondents (69,4%), respondents with working period of more than 5 years were 54 respondents (36,5%), Responden with awkward working position category as many as 56 respondens (65,9%). The results of the analysis show that there is a relation between individual factors (age, BMI, smoking habit and years of work) with complaints of low back pain (p-value 0,000) and a relation between job factors (working position) with complaints of low back pain (p-value 0,000).